2021
DOI: 10.1088/1748-9326/ac1cbb
|View full text |Cite
|
Sign up to set email alerts
|

Improving seasonal predictions of meteorological drought by conditioning on ENSO states

Abstract: Useful hindcast skill of meteorological drought, assessed with the 3-month standardized precipitation index (SPI 3 M ), has been so far limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…El Niño Southern Oscillation (ENSO) and other large-scale climate events such as Pacific Decadal Oscillation (PDO) have substantial impacts on the occurrence and development of regional and global droughts (Özger et al, 2009;Wang & Arun, 2015;Wang et al, 2019;Gore et al, 2020;Nguyen et al, 2021;Pieper et al, 2021). Sun and Yang (2012) found that the interactions between La Nina, North Atlantic Oscillation (NAO), and thermal conditions of the Qinghai-Tibet Plateau triggered severe droughts in southern China in spring.…”
Section: Introductionmentioning
confidence: 99%
“…El Niño Southern Oscillation (ENSO) and other large-scale climate events such as Pacific Decadal Oscillation (PDO) have substantial impacts on the occurrence and development of regional and global droughts (Özger et al, 2009;Wang & Arun, 2015;Wang et al, 2019;Gore et al, 2020;Nguyen et al, 2021;Pieper et al, 2021). Sun and Yang (2012) found that the interactions between La Nina, North Atlantic Oscillation (NAO), and thermal conditions of the Qinghai-Tibet Plateau triggered severe droughts in southern China in spring.…”
Section: Introductionmentioning
confidence: 99%